Workplace Diversity and Inclusion Practices: Effects on Team Creativity and Organizational Performance - Rama, Rovanita; Yusuf, Ramdan; Siagian, Ade Onny (International Journal of Business, Law, and Education, 2025)
This study examines the relationship between workplace diversity practices, inclusion, team creativity, and organizational performance in modern organizational settings. Drawing on theories of Information–Decision Making, Social Categorization, and the Resource-Based View, the research explores how diversity contributes to creativity and performance, and how inclusion moderates these effects. Using a quantitative research approach, data were collected from 312 employees working across multiple industries using structured online questionnaires with validated measures. Results analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM) reveal that workplace diversity has a positive and significant influence on inclusion and team creativity. Inclusion also strongly predicts both team creativity and organizational performance, while team creativity significantly contributes to organizational performance. Furthermore, inclusion partially mediates the relationship between diversity and both creativity and performance, demonstrating its essential role in unlocking the strategic benefits of diversity. These findings highlight that diversity initiatives yield positive outcomes only when embedded within inclusive organizational cultures. The study contributes to ongoing discussions on human capital management and offers practical implications for leaders seeking to improve innovation and long-term competitive advantage through inclusive diversity strategies.